PENGEMBANGAN INSTRUMEN UNTUK MENGUKUR SELF EFFICACY SISWA DALAM PEMBELAJARAN KIMIA - Hairida Hairida (EDUSAINS, 2017)
Abstract The characteristics of learners in learning need to get the attention from the teacher. However, the measurement of self-efficacy has not been implemented by teacher, and instrument to measure these capabilities are not available, and teachers do not understand the importance of information about students' self efficacy. The main aim of this development research is to produce a tool or instrument ratings whivch are valid, reliable and practical to measure self-efficacy in learning chemistry in junior high school. The method used in this research is the development methods. The results of this research is the availability of a viable instrument which can used to measure students’ self-efficacy in learning chemistry in junior high school, which qualifies as a valid, reliable, and practical test. Keywords: self efficacy; chemistry learning Abstrak Karakteristik siswa dalam belajar perlu mendapatkan perhatian para guru. Namun, pengukuran self efficacy selama ini belum dilaksanakan oleh guru, dan instrumen  untuk mengukur kemampuan tersebut belum tersedia serta guru belum memahami pentingnya informasi tentang self efficacy siswa. Penelitian pengembangan ini bertujuan utama untuk menghasilkan alat atau instrumen penilaian yang valid, reliabel dan praktis untuk mengukur self efficacy dalam pembelajaran kimia di SMP.  Metode penelitian yang digunakan dalam penelitian ini adalah  metode penelitian pengembangan. Hasil penelitian ini ialah tersedianya instrumen yang layak digunakan untuk mengukur self efficacy siswa dalam pembelajaran kimia di SMP, yang memenuhi persyaratan sebagai tes yang valid, reliabel, dan praktis. Kata Kunci: self efficacy;  pembelajaran kimia  Permalink/DOI: http://dx.doi.org/10.15408/es.v9i1.4000